Learning Technique to Transform 2 Dimension Technical Drawing to 3 Dimension Technical Drawing for Basic Technical Drawing Class - Porncharoen, Ratthai; Kansomkrait, Lui; Krutasaen, Watanapun (Journal of Fine and Applied Arts Khon Kaen University, 2021)
This article is part of the research from 360107 Basic Technical Drawing Class aim to teach skills to understand, distinguish and develop between 2 Dimension Technical Drawing to 3 Dimension Technical Drawing. This class is offered to the 1st year student of department of Product design, Faculty of Decorative Arts, Silpakorn University. In This article,the researchers used only the works of the pretest sample of the student before the beginning of this course to interpret the thinking technique between 2 Dimension Technical Drawing and 3 Dimension Technical Drawing present in various perspective angle of simpliflied geometric forms in square cube only in order to have students convey the Technical Drawing from 2 Dimension to 3 Dimension in a given box structure and also 2D shape with front, side and top views will be given to create an end Technical Drawing result. The total out come of the student’s works shown that there are a few correct answer of the 3D Technical Drawings but fairly understand of 2D Drawing but still some misinterpret in directions. The objective on pre evaluation of the students understanding of Technical Drawings dimensions is to best preparations of the content and direction of this course. From many years experiences in teaching this course indicate that not because of the student’s abilities to draw but their lack of learning experience in this practice and the instant test. After the reseacher reveal the right answer to the problem and demonstrate with a few simple example and let the students think and draw step by step , they gradually gain experiences through learning and practicing but still need more time to advance in a more complex 3D Drawing. 10-20 sample of drawings will be used in each test rotate appropriately around each semester. Teaching outcomes at the end of the semester : after students have practiced and gained more learning experience in understanding to read more Technical Drawings, they can achieve to reach the more difficult and complex problem with the high score of the expectation of the Instructor.